2022
DOI: 10.1177/20406223221102803
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implication of noninvasive right ventricle-to-pulmonary artery coupling in chronic thromboembolic pulmonary hypertension

Abstract: Aims: Impairment of right ventricle-to-pulmonary artery coupling (RV-PA coupling) is a major determinant of poor prognosis in patients with pulmonary hypertension. This study sought to evaluate the ability of an echo-derived metric of RV-PA coupling, the ratio between tricuspid annular plane systolic excursion (TAPSE), and pulmonary artery systolic pressure (PASP) and to predict adverse clinical outcomes in chronic thromboembolic pulmonary hypertension (CTEPH). Methods and results: A total of 205 consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…which are strong predictors of adverse outcomes in PH (19). According to our results, RV function showed signi cant negative correlation with AHI and the RV-PA Coupling by Ees/Ea calculation.Tello et al (18) proved that the coupling of RV-PA has considerable reserve, as Ees/Ea has to decrease from normal values of 1.5 to 2 to < 0.8 before RV maladaptation…”
supporting
confidence: 58%
See 1 more Smart Citation
“…which are strong predictors of adverse outcomes in PH (19). According to our results, RV function showed signi cant negative correlation with AHI and the RV-PA Coupling by Ees/Ea calculation.Tello et al (18) proved that the coupling of RV-PA has considerable reserve, as Ees/Ea has to decrease from normal values of 1.5 to 2 to < 0.8 before RV maladaptation…”
supporting
confidence: 58%
“…Duan, X Li et al 2022 evaluate the ability of an echocardiography derived RV-PA coupling using TAPSE/ PASP ratio to predict adverse clinical outcomes in chronic thromboembolic pulmonary hypertension (CTEPH) and concluded that low TAPSE/PASP identi es patients with a high risk of clinical deterioration, and this novel metric could be applicable for risk strati cation in CTEPH, the study also proved that the TAPSE/PASP ratio was signi cantly related to PVR and Pulmonary arterial compliance,…”
mentioning
confidence: 96%
“…Nevertheless, the TAPSE/sPAP has been shown to be associated with clinical deterioration, hemodynamics, functional class, disease severity and adverse outcomes [21,22] . It was also found that the TAPSE/sPAP could be applicable for risk strati cation in CTEPH patients [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the TAPSE/sPAP has been shown to be associated with clinical deterioration, hemodynamics, functional class, disease severity and adverse outcomes [21,22] . It was also found that the TAPSE/sPAP could be applicable for risk strati cation in CTEPH patients [21] . Our results further demonstrated that the TAPSE/sPAP could be an independent predictor of prognostic risk strati cation for precapillary PH patients.…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent standard transthoracic echocardiography conducted by experienced cardiologists as previously detailed [ 14 ]. The left ventricular ejection fraction was calculated using the Simpson biplane method.…”
Section: Methodsmentioning
confidence: 99%